Expression of TNF-α and TGF-β after the Administration of Cacao Bean Extract on Alveolar Bone - Rina Sujiati; Depi Praharani; Sulistiyani; Atik Kurniawati; Dessy Rachmawati; Dwi Prijatmoko; Rudy Joelijanto; Shierin Velly Fiolita; Firda Qurrotul Aini Rasyid; Lilis Nurhalifah; Syafika Nuring Fadiyah; Millenieo Martin (ziauddin University, 2024)
Background: Teeth that are given orthodontic forces can relapse because of excessive resorption on the pressure side. Cocoa bean extract enhances bone apposition during bone remodeling by increasing osteoblast proliferation. This research aimed to ascertain molecular mechanisms of alveolar bone during orthodontic tooth movement applied with cacao bean extract (Theobroma cacao L.) through TNF-α and TGF-β, expressions. Methods: This study utilized an experimental laboratory posttest-only control group design. The NiTi closed coil spring was braced between the right upper first molar and the upper incisor, a strength of 10gf was estimated utilizing a tension gauge to mesially move the upper molars. The total 36 were divided into six groups, Wistar rats were beheaded on days 7 and 14 of treatment. Immunohistochemical staining was utilized to show TNF-α and TGF-β expression. Results were assessed using the one-way ANOVA analysis. Results: The immunohistochemistry findings in osteoclast cells that demonstrate positive results for TGF-β and TNF-α, expression by immunohistochemical staining calculated for each group (control, positive control, treatment).  The treatment group (Q14) showed reduced expression (2±0.957) of TNF-α in osteoclast cells. TGF-β, on the other hand, was found with diminished expression in osteoblast cells C-7 and C-14 (3.75±0.816, 3.25±0.957) and increases in the treatment group (Q14) (11.25±0.957). significantly (p=0.000).   Conclusion: The administration of cacao bean extract on days 7 and 14 could decrease the expression of TNF-α and increase TGF-β of the treatment group. Therefore, with an increased TNF-α apposition process, relapse after orthodontic treatment can be prevented to accelerate the orthodontic treatment.